Skana, an orca whale, performs at the Vancouver Aquarium, circa 1975 - University of Washington Libraries, Special Collections Division
On verso of image: Skana, a 17 foot killer whale, in the BC Tel Pool of the Vancouver Public Aquarium. Filed in British Columbia--Vancouver In 1967 a killer whale named Walter, which had been caught off the Washington coast, was brought to Vancouver for the annual Boat Show. The whale was purchased by the Aquarium and, when it was realized that he was a she, renamed Skana. Skana soon became the Aquarium’s star attraction. The following year a group of whales were caught in Pender Harbour. A small male originally called Peanuts and later named Hyak was purchased and brought to the Aquarium. Hyak would be Skana’s companion until her death in 1980.